21st century retro: Mad Men and 1960s America in film and television - Baruah, Debarchana (American culture studies, 2021)
Numerous contemporary televisual productions revisit the past but direct their energies towards history's non-events and anti-heroic subjectivities. Debarchana Baruah offers a vocabulary to discuss these, using Mad Men as a primary case study and supplementing the analysis with other examples from the US and around the world. She takes a fundamentally interdisciplinary approach to studying film and television, drawing from history, memory, and nostalgia discourses, and layering them with theories of intertextuality, paratexts, and actor-networks. The book's compositions style invites discussions from scholars of various fields, as well as those who are simply fans of history or of Mad Men.
Literaturverzeichnis: Seite 213-244
Keywords: Hochschulschrift; Mad Men; Geschichte 1960-1970; USA